A política de cotas na UEPG: em busca da democratização da educação superior - Krainski, Luiza Bittencourt (2013)
The present study refers to one of the central themes in higher education: the spreading and democratization of access to university courses. The general aim of this research consists in following the actions of the State University of Ponta Grossa, Paraná, with regards to the Policy of Quotas, to identify the advances and difficulties. Introduced in the period from 2007 to 2014, it continued for another eight years starting as from 2015. Understanding the factors that interfere in the academic path of the students from different courses, is fundamental for elaborating policies which give ample rights to education. The introduction of affirmative actions, among which the Policy of Quotas in the universities, are one of the actions whose aim is to favor students from state schools and black students. The concept supporting this work is that the process of democratization includes the access of the students, the permanence as well as the quality of the actions worked on. For this research, a case study of the exploratory type was done as it was thought that this type of research allows to gather information from a contemporary phenomenon in its real life context. The methodology included a bibliographic revision, a documental research with official documents from international organizations, national legislation, government plans and programs, laws and institutional documents from the State University of Ponta Grossa, semi-structured interviews and open questionnaires. The data collected was seen under the perspective of content analysis, obeying the phases of ordering, classifying and data analysis. The subjects who were interviewed were administrators who took part in the process of implanting the Policy of Quotas and current representatives of entities connected to the policy as well as students entering university by means of the Policy of Quotas in courses which present greater or lesser demand of candidates in the university entrance examination. The different tools used with administrators and students allowed to identify fundamental elements for the construction of categories of analyses. The results of this study show that the Policy of Quotas at the State University of Ponta Grossa favor the access of students from state schools and in smaller number, black students. During the university trajectory, these students present difficulties concerning knowledge acquired in elementary and secondary school but which they try to overcome in collective studies. Entrance into university is accompanied by a process of affiliation, institutional and intellectual. Nevertheless, this trajectory is not followed by an institutional policy which helps to keep these students at university. With regards to quota students and administrators, this research tries to contribute in the improvement of institutional action and policies related to the permanence and monitoring of the students in the institution